State school finance inequities and the limits of pursuing teacher equity through departmental regulation - Bruce D. Baker; Mark Weber (Arizona State University, 2016)
New federal regulations (State Plans to Ensure Equitable Access to Excellent Educators) place increased pressure on states and local public school districts to improve their measurement and reporting of gaps in teacher qualifications across schools and the children they serve. Yet a sole focus on resource disparities between schools within a state ignores an important driver of those disparities: district-level spending variations, particularly when accounting for differences in student populations. The analyses herein evaluate connections between district and school level spending measures and teacher equity measures (such as salary competitiveness and staff: student ratios), and specifically whether inequality in "access to excellent educators" at the school level is greater in states where funding inequalities between school districts are greater. We find that district spending variation explains an important, policy relevant share of school staffing expenditures in 13 states. In many states, including Illinois and New York, a nearly 1:1 relationship exists between district spending variation and school site spending variation. In California, Illinois, Louisiana, New York, Ohio, Pennsylvania and Virginia, district spending is positively associated with competitive salary differentials, average teacher salaries, and numbers of certificated staff per 100 pupils. In each of these states, district poverty rates are negatively associated with competitive salary differentials, average teacher salaries and numbers of certified staff per 100 pupils. As such, regulatory intervention without more substantive changes to state school finance systems, addressing district-level inequities, will likely achieve little. Current federal policy pressures state education agencies to report and attempt to regulate inequities that arise because of school finance systems over which those agencies have no direct influence. Our analysis suggests that the administration would be more likely to meet its goals if it attempted to more directly address state school finance system disparities, placing pressure on state legislatures to equitably and adequately fund schools, and following through with the requirement that state-to-district equity provisions translate into district-to-school equity.